Land use evolution and management under recurrent conflict conditions: Umbundu agroforestry system in the Angolan Highlands. (January 2015) - Delgado-Matas, Cristobal; Mola-Yudego, Blas; Gritten, David; Kiala-Kalusinga, David; Pukkala, Timo
Highlights: The paper analyses the effects of long term armed conflicts on traditional land uses. The system main goal: to assure continuous food supply under changing ownership and security. System constrains are soil fertility, and water availability and manure/fertilizer. The study has implications for land use and conflict management in Angola and beyond. Abstract: The article analyzes the effects of long term armed conflicts on the characteristics and evolution of traditional land uses. The main focus is on the Umbundu agroforestry system, an endogenous and dynamic traditional African land use in the Angolan Central Highlands, an area that has experienced numerous conflicts during the last 200 years. The study used field research and a literature review to analyze the historical evolution of the system and its recovery after the conflicts. The results provided a characterization of the system's main traits and stakeholders through time. The main focus of the system was maintaining a continuous supply of food crops under changing ownership and security, constrained by soil fertility, and the availability of water and fertilizers. Land use conflicts moulded the system, allowing it to be rich during low and medium intensity conflicts, though constraining it when conflicts escalated to a military civil war. The evolution of the land use system was examined using the frame of multi-functionality. Additional focus is made on its current and future challenges to become a sustainable and profitable agrarian land use system. The study has implications for land use management (e.g. regarding the length of fallow period) as well as conflict management.